PENGGUNAAN E-RESOURCES OLEH MAHASISWA ILMU PERPUSTAKAAN SELAMA PANDEMI COVID 19 - Rahmi, Lailatur (UIN Imam Bonjol Padang, 2021)
ABSTRACT One of the key components to support the learning process in higher education is the effectiveness and practicality of finding information resources, both printed and electronic. The emergence of the use of information technology services brings tremendous changes in the processing and retrieval of information. Electronic resources are now used more often than print resources. This study uses an online survey designed to explore the situation of users in using electronic resources offered by the UIN Imam Bonjol Padang Library during the COVID-19 pandemic in the 2020/2021 academic year. This research is an attempt to understand the awareness and use of e-resources in academic libraries and to find out the problems faced by librarians and users in accessing e-resources. This study uses a descriptive quantitative research approach and uses a questionnaire as the main instrument for data collection. Online surveys are distributed using Google Forms through various social media platforms. The population is active students of the Faculty of Adab and Humanities totaling 60 people. The results of the study show that the use of electronic resources is still minimal during this critical period. Most students use electronic resources only to update knowledge and fulfill lecture assignments and very few refer to them for writing scientific papers or final assignments. Databases as well as electronic journals are the most preferred resources. The results and recommendations of this study are expected to be useful for the UIN Imam Bonjol Padang Library, especially in terms of knowing the problems they face when looking for electronic resources. ABSTRAK Salah satu komponen kunci penunjang proses pembelajaran pada pendidikan tinggi adalah keefektifan dan kepraktisan dalam penemuan sumber daya informasi, baik tercetak maupun elektronik. Munculnya penggunaan layanan teknologi informasi membawa perubahan luar biasa dalam pemrosesan dan pencarian informasi. Sumber daya elektronik sekarang lebih sering digunakan daripada sumber daya cetak. Penelitian ini menggunakan sebuah survei online yang dirancang untuk mengeksplorasi situasi pemustaka dalam menggunakan sumber daya elektronik yang ditawarkan oleh Perpustakaan UIN Imam Bonjol Padang selama pandemi COVID-19 di tahun ajaran 2020/2021. Penelitian ini merupakan upaya untuk memahami kesadaran dan penggunaan e-resources di perpustakaan akademik dan untuk mengetahui masalah yang dihadapi oleh pustakawan dan pengguna dalam akses e-resources. Penelitian ini menggunakan pendekatan penelitian kuantitatif deskriptif dan menggunakan kuesioner sebagai instrumen utama untuk pengumpulan data. Survei online didistribusikan menggunakan Google Formulir melalui berbagai platform media sosial. Populasi adalah Mahasiswa aktif Fakultas Adab dan Humaniora berjumlah 60 orang. Hasil penelitian menunjukkan masih minimnya penggunaan sumber daya elektronik selama masa kritis ini. Sebagian besar mahasiswa menggunakan sumber daya elektronik hanya untuk update pengetahuan dan memenuhi tugas perkuliahan dan sedikit sekali yang merujukanya untuk penulisan karya ilmiah atau tugas akhir. Database serta jurnal elektronik adalah sumber daya yang paling disukai. Hasil dan rekomendasi penelitian ini diharapkan dapat bermanfaat bagi Perpustakaan UIN Imam Bonjol Padang, khususnya dalam hal mengetahui masalah yang mereka hadapi ketika mencari sumber daya elektronik.